2009
DOI: 10.1227/01.neu.0000345952.64041.9c
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of Ligaments Near the Foramen Ovale

Abstract: Such anomalous bony obstructions could interfere with transcutaneous needle placement into the foramen ovale or distort anatomic relationships during approaches to the cranial base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 15 publications
2
67
1
Order By: Relevance
“…Directly inferior to the exocranial surface of the FO, two ossified ligaments, known as the pterygospinous bar and the pterygoalar bar, are found in some cases. The prevalence of the pterygospinous bar, also known as the ligament of Civinini, has been reported as 2.6 - 17%, while that of the pterygoalar bar, also known as the ligament of Hyrtl, has been reported as 2.6 - 30% [5-6]. These bars can be unilateral and/or extend additionally over the foramen spinosum [7].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Directly inferior to the exocranial surface of the FO, two ossified ligaments, known as the pterygospinous bar and the pterygoalar bar, are found in some cases. The prevalence of the pterygospinous bar, also known as the ligament of Civinini, has been reported as 2.6 - 17%, while that of the pterygoalar bar, also known as the ligament of Hyrtl, has been reported as 2.6 - 30% [5-6]. These bars can be unilateral and/or extend additionally over the foramen spinosum [7].…”
Section: Reviewmentioning
confidence: 99%
“…However, anatomical variations should be kept in mind, as Tubbs et al reported cases of elongated or enlarged sphenoid spines that can obstruct and prevent glycerol rhizolysis [5]. Anatomical variations of the ligaments of Civinini and Hyrtle can also have clinical implications; if they compress the branches of the mandibular nerve, mastication weakness and sensory loss can result [6].…”
Section: Reviewmentioning
confidence: 99%
“…Thus, the knowledge of the ossified pterygospinous ligament is important for surgeons for planning surgical procedures and who perform invasive procedures in/near infratemporal fossa would IJBR (2014) 05 (09) www.ssjournals.com increases the success rate of the surgical procedures 25 . Also important for anaesthetists and neurosurgeons since anomalous bony obstructions could interfere positioning the needle during transfacial needle approaches to foramen ovale 3 . Therefore, the knowledge of Anatomical variation of the pterygospinous ligament-ossification is clinically important to radiologists and neurosurgeons, maxillofacial and dental surgeons, and anaesthetists along with academically for anatomists and anthropologists.…”
Section: Resultsmentioning
confidence: 99%
“…In 1837, Civinini described the pterygospinous ligament and found that this ligament ossified in 2% to 3% of his specimen 2 . The pterygospinous ligament and ossified foramen formed is named after Civinini 3 .…”
Section: Introductionmentioning
confidence: 99%
“…11 The FO is relatively small and anatomical variations including foramen stenosis, or ossified pterygospinous or pterygoalar ligaments may complicate the cannulation of the already-small target. 12,13 Likewise, the shape of the FO may contribute to operative difficulties. 14 The diverse shapes of foramina ovalae have been described as “banana-like,” “triangular,” “oval,” “truly oval,” “elongated oval,” “elongated,” “semicircular,” “almond,” “round,” “rounded,” “slit,” “irregular,” “D shape,” and “pear”.…”
Section: Introductionmentioning
confidence: 99%